Bi-modal dose-dependent cardiac response to tetrahydrobiopterin in pressure-overload induced hypertrophy and heart failure - Moens, A; Ketner, E; Takimoto, E; Schmidt, T; O'Neill, C; Wolin, MS; Alp, N; Channon, K; Kass, D (2011)
The exogenous administration of tetrahydrobiopterin (BH4), an essential cofactor of nitric oxide synthase (NOS), has been shown to reduce left ventricular hypertrophy, fibrosis, and cardiac dysfunction in mice with pre-established heart disease induced by pressure-overload. In this setting, BH4 re-coupled endothelial NOS (eNOS), with subsequent reduction of NOS-dependent oxidative stress and reversal of maladaptive remodeling. However, recent studies suggest the effective BH4 dosing may be narrower than previously thought, potentially due to its oxidation upon oral consumption. Accordingly, we assessed the dose response of daily oral synthetic sapropterin dihydrochloride (6-R-l-erythro-5,6,7,8-tetrahydrobiopterin, 6R-BH4) on pre-established pressure-overload cardiac disease. Mice (n = 64) were administered 0-400. mg/kg/d BH4 by ingesting small pre-made pellets (consumed over 15-30. min). In a dose range of 36-200. mg/kg/d, 6R-BH4 suppressed cardiac chamber remodeling, hypertrophy, fibrosis, and oxidative stress with pressure-overload. However, at both lower and higher doses, BH4 had less or no ameliorative effects. The effective doses correlated with a higher myocardial BH4/BH2 ratio. However, BH2 rose linearly with dose, and at the 400. mg/kg/d, this lowered the BH4/BH2 ratio back toward control. These results expose a potential limitation for the clinical use of BH4, as variability of cellular redox and perhaps heart disease could produce a variable therapeutic window among individuals. This article is part of a special issue entitled "Key Signaling Molecules in Hypertrophy and Heart Failure". © 2011 Elsevier Ltd.